Eksistensialisme Sartre dalam Tokoh Perempuan Novel Sputnik Sweetheart Karya Haruki Murakami - Ridwan Ridwan; Nensilianti Nensilianti; Arianti Talib (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research aims to analyse the female characters in Haruki Murakami's Sputnik Sweetheart, namely Sumire and Miu, through the lens of Jean-Paul Sartre's existentialism. The main focus is on Sartre's three concepts of existentialism. The method used is a qualitative method with a text analysis approach. Several excerpts from the novel were selected and analysed based on Sartre's concept of existentialism. The analysis includes the identification and interpretation of key moments in the narrative that reflect existence for the self (être-pour-soi), existence in the self (être-en-soi), and bad faith (mauvaise foi or bad faith). The results show that the characters Sumire and Miu illustrate Sartre's existentialism concepts in depth about the existential struggle in dealing with their freedom, identity, and personal responsibility. The findings provide insights that can be applied to understanding the complexity of human relationships and the search for the meaning of life in the context of modern literature.